Reactive oxygen species influence nerve growth factor synthesis in primary rat astrocytes - Naveilhan, P; Neveu, I; Jehan, F; Baudet, C; Wion, D; Brachet, P (Journal of neurochemistry, 1994)
Newborn rat brain astrocytes, cultured in a serum-free medium, were exposed for 30 min to two types of reactive oxygen species. Cells were either treated with the xanthine/xanthine oxidase (X/XOD) system, which generates both H2O2 and the O2.- radical, or to H2O2 alone. Both treatments induced a dose-dependent accumulation of nerve growth factor (NGF) transcripts, 6 h after the exposure. Maximal effect was obtained with 6 mU/ml XOD, or 10(-4) M H2O2. A rapid expression of protooncogenes of the jun and fos families was also noticed in X/XOD- or H2O2-treated cells. This phenomenon was transient in cells exposed to X/XOD. However, in the case of H2O2-treated cells, the accumulation of c-fos or c-jun mRNAs was still pronounced 6 h after the end of the treatment and the levels of cell-secreted NGF appeared relatively reduced, when compared with those obtained after a shock with the X/XOD system. This raised the possibility that H2O2 at 10(-4) M could depress protein synthesis. Measurements of the incorporation of radiolabeled amino acids into trichloroacetic acid-precipitable material supported this assumption. Level of radioactivity associated with cellular material was dramatically reduced in H2O2-treated cells, when it was compared with control or X/XOD-treated cells. Furthermore, treatment of cells with the protein synthesis inhibitor anisomycin had an effect similar to that of H2O2 because it caused an accumulation of c-fos, c-jun, and NGF transcripts after 6 h of treatment.